1992
DOI: 10.1161/01.cir.86.4.1206
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and outcome of patients with high defibrillation thresholds. A multicenter study.

Abstract: BACKGROUND Successful defibrillation by an implantable cardioverter-defibrillator (ICD) depends on its ability to deliver shocks that exceed the defibrillation threshold. This study was designed to identify clinical characteristics that may predict the finding of an elevated defibrillation threshold and to describe the outcome of patients with high defibrillation thresholds. METHODS AND RESULTS The records of 1,946 patients from 12 centers were screened… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
84
2
4

Year Published

1999
1999
2017
2017

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(90 citation statements)
references
References 66 publications
0
84
2
4
Order By: Relevance
“…It is possible that there are characteristics of cardiac arrest that are unique to patients with CKD. For example, CKD is associated with high defibrillation thresholds (22), which, in itself, has been linked to poor survival (27). Third, our study design might not allow for the complete capture of relevant events.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that there are characteristics of cardiac arrest that are unique to patients with CKD. For example, CKD is associated with high defibrillation thresholds (22), which, in itself, has been linked to poor survival (27). Third, our study design might not allow for the complete capture of relevant events.…”
Section: Discussionmentioning
confidence: 99%
“…Early data has suggested that some deaths in ICD patients occur mostly in those with high DFTs. 19,20) Rubenstein, et al demonstrated that an elevated DFT is a significant independent predictor of the overall mortality and DFT provides incremental information about the mortality and prognosis. Further, they also showed that an elevated DFT is associated with increased mortality even in the setting of an adequate safety margin.…”
Section: Resultsmentioning
confidence: 99%
“…Careful testing of DFTs should be performed in all the patients, with special attention to those who have monophasic waveform ICDs, those with an epicardial lead system 39 , patients with a high DFT at baseline, and patients treated with high dose, 40 chronic amiodarone. [41][42][43][44] Azimilide has been shown to have minimal effects on the DFT or pacing thresholds in ICD patients. 24,45 Similarly, dronedarone has been shown to have no effect on defibrillation safety margin or pacing thresholds at its therapeutic dose or higher.…”
Section: Drug-device Interactionmentioning
confidence: 99%